The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1159/000246399
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Medial Telangiectatic Vascular Nevus: A Study of 43 Children

Abstract: Background: Medial telangiectatic vascular nevi are capillary vascular malformations frequently observed at birth occurring mostly on the face or on the nape as a single lesion or as multiple macules affecting more than one site simultaneously. In 1990, Metzker and Shamir reported a medial telangiectatic vascular nevus (MTVN) in the sacral region along the midline and called this particular variety of MTVN ‘butterfly-shaped mark’. Objective: Our study was performed to investigate the morphology and localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
2
12
0
3
Order By: Relevance
“…[6][7][8] The screening value of isolated lumbosacral vascular lesions remains difficult to determine because, despite the International Society for the Study of Vascular Anomalies (ISSVA) classification, ambiguity persists in the terminology used in the literature. [9][10][11][12][13][14] At present, the importance of dimples is still under discussion. [15][16][17] Furthermore, no one has established whether isolated deviation of the gluteal furrow (DGF) represents a cutaneous marker of OSD.…”
mentioning
confidence: 99%
“…[6][7][8] The screening value of isolated lumbosacral vascular lesions remains difficult to determine because, despite the International Society for the Study of Vascular Anomalies (ISSVA) classification, ambiguity persists in the terminology used in the literature. [9][10][11][12][13][14] At present, the importance of dimples is still under discussion. [15][16][17] Furthermore, no one has established whether isolated deviation of the gluteal furrow (DGF) represents a cutaneous marker of OSD.…”
mentioning
confidence: 99%
“…Our case series emphasizes that NS can involve multiple anatomic sites beyond the ''classic'' locations of the nape, glabella, and eyelids, an observation noted in several previous studies. 1,2,4,8,10,15,17,[19][20][21][22][23][24][25][26] Atypical locations included the left and right side of the forehead, nasal bridge, nose, columella, philtrum, upper cutaneous lip, vermillion, lower cutaneous lip, as well as upper, middle, and lower back (Figs 3 and 4). The differentiation of NS from port-wine stains in these areas is much easier when the typical sites are also affected, as was the case in all of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings as well as those in previous reports do serve, however, to emphasize that these sites are part of the spectrum of NS. 1,8,17,21,22,24,25 The natural history of NS is of spontaneous fading in the majority of patients, although NS involving the nape, and occasionally other sites, may persist. 1,3,4,13,17,20 Pasyk et al 17 reported 6 families with persistence of NS beyond infancy and autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…In congenital cases, medial telangiectatic nevi are not uncommon [1]. Recently, their possible association with the autosomal dominant Williams syndrome has been discussed [2].…”
Section: Introductionmentioning
confidence: 99%